Design and Deployment of Backend Integration System for Rumah Jurnal Using ExpressJS - Hamami, Muhammad Syamil; Rifqi Syamsul Fuadi (CoreID Journal, 2024)
The design and deployment of a backend integration system for Rumah Jurnal at UIN Sunan Gunung Djati Bandung addresses the increasing complexity of journal management systems across faculties. A centralized platform enhances accessibility and operational efficiency by consolidating multiple journal databases into a unified interface. Developed using ExpressJS, the system ensures reliable data synchronization and robust management through an API-driven architecture, security measures, and deployment on a Virtual Private Server (VPS) with Nginx and PM2. Testing demonstrates significant performance improvements, including faster response times and seamless user experiences, positioning the system as an effective solution for modernizing journal management.